Point of Care Ultrasound Diagnosis of Pseudoaneurysm of an Upper Extremity Arteriovenous Dialysis Graft - Forrest Lindsay-McGinn; Nathaniel C. Reisinger (CINQUILL Medical Publishers Inc., 2022)
We describe the rapid diagnosis with point of care ultrasound (POCUS) of two acute pseudoaneurysms of a bovine arteriovenous dialysis graft with superimposed cellulitis in a 44-year old male patient who presented with pain over his upper arm graft site. POCUS evaluation decreased the time to diagnosis and vascular surgery consultation.